Jumping performance differences among competing elite female handball players with or without previous ACL reconstruction - Setuain, I.; Millor, N.; Alfaro, J.; Gorostiaga, E.; Izquierdo, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Spain Female handball players are one of the most exposed athletes to the ACL injury. Persisting strength and neuromuscular control deficits may be observed among the athletes who had suffered this injury, despite having complete the rehabilitation process due to inadequate or incomplete rehabilitation. This factor could be one of the explaining reasons for the ACL reinjury rates among this population. Measuring jumping performance such as stance phase contact times or jump height during the rehabilitation process would help to minimize high-cost reinjury rate among female handball elite athletes. PURPOSE: To describe jumping performance among a group of 20 female handball elite athletes using a previously validated jump test battery. Secondly, to Identify possible differences between injured and uninjured extremities, in jump height, stance phase contact time, and reached distance obtained. We hypothesized that previously injured extremities would show deficits in jumping performance despite the injured athletes have completed their rehabilitation process and being competing at the maximum level. METHODS: 20 female elite athletes (6 previously injured and reconstructed and 14 uninjured subjects) were evaluated performing a previously validated jump test battery that includes bilateral drop jump, unilateral drop jump, unilateral countermovement jump, unilateral triple jump for distance and the cross over hop for distance. Height (m), flight time (s), stance phase contact time (s) and distance (m) were obtained in each jump test performed. For the unilateral jump tests, comparison was made between reconstructed legs and the dominant ones of the uninjured subjects. For the bilateral drop jump test, comparison was made between reconstructed and uninjured subjects. RESULTS: Previously ACL reconstructed athletes demonstrated significantly lower bilateral drop jump flight time (0,393 vs 0,541 s; P<0.001) and less distance reached in triple leg hop for distance (0,382 vs 0,435 m; P<0.05) on their reconstructed leg compared with the healthy legs of the uninjured subjects. No significant differences were observed in the other variables recorded CONCLUSION: Previously ACL reconstructed athletes may cope with some functional deficits once returning to competition, potentially increasing their reinjury risk. Restoration of these deficits would help to decrease the reinjury rates among this population.